Asociación de materia orgánica y minerales en suelos Amazónicos: Un estudio espectroscópico - Clabel H y Cols., José L. (2018)
The associations between organic and mineral matter, in the different Amazonian soils profile from the São Gabriel da Cachoeira region, were studied. We collected nine samples up to a depth of 4 meters. The whole soil was studied by elemental analysis, X-ray diffraction and FTIR spectroscopy. According to results, elemental analysis is a satisfactory method for the quantification of carbon, because of its precision and reproducibility. The mineralogical analysis of the whole soil showed that the Quartz and Kaolinite, is the main constituent for the studied horizons of A1 for Bhs (depth 0 to 214 cm) and Tr for K2 (depth 215 to 290 cm), respectively. As a consequence of the structural changes, there is evidence of spectroscopic changes that are reflected in the aromatic and aliphatic functional groups.